Extraordinary ductility enhancement of Mg-Nd-Zn-Zr alloy achieved by electropulsing treatment - Xiang Wang; Baoxue Zhou; Hua Huang; Jialin Niu; Shaokang Guan; Guangyin Yuan (Journal of Magnesium and Alloys)
Mg-Nd-Zn-Zr (JDBM) alloy was studied as a candidate for biodegradable implant material because of its moderate mechanical properties, good biocompatibility, and favorable uniform degradation behavior. To verify whether JDBM alloy exhibits electroplasticity effect and then study the mechanism of electropulsing treatment on JDBM alloy, in this study, homogenized and pre-tensile deformed samples were treated by electropulsing. After the electropulsing treatment, the average grain size was refined due to recrystallization, micron-scale Mg12Nd secondary phases precipitated slightly, while the morphology of nanoscale Zr particles changed from rodlike to ellipsoidal shape. The elongation to failure (EL) increased obviously for the homogenized and pre-tensile deformed JDBM alloy samples after electropulsing treatment, accompanying with no obvious sacrifice of the yield strength (YS) for the former and an evident decrease of YS for the latter, mainly due to the reduction of the dislocation density. The YS decrement and EL increment (77.57%) for the latter are more apparent attributed to the higher density of dislocations introduced by pre-tensile deformation. Therefore, the electropulsing treatment can obviously improve the mechanical properties of JDBM alloy, especially for the plasticity. The present work opens a new window for the fabrication of JDBM alloy profiles with high mechanical properties, especially for the plasticity, such as the cold drawing wires and tubes for biomedical applications. It also could provide theoretical references for other magnesium alloy processing.